Жмурик - проказник: повесть / Э. Веркин - Веркин Эдуард (Серия "Кошмарики", 2005)
Экземпляры: (20181010) / Инвентарный номер: 31547 / Цена: 27.80 / Сис.шифр: Р2 / Авт.знак: В32 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6